Studies on Hatching and Early Larval Survival of Marble Goby Oxyeleotris marmoratus for Improvement of the Production Techniques - Nguang, S. I (2014)
Marble goby Oxyeleotris marmoratus, is a popular aquaculture target in Southeast Asia. Although marble goby is a freshwater species, some are known to stay in brackish water during their early life stage. Also, it has been reported that growth and survival of artificial produced larvae is better in 10 psu than in freshwater (FW). However, the suitable conditions for embryonic development and early larval stage remained unknown. To improve hatching and early larval rearing technique, a series of experiments was carried out to determine the optimum salinity and temperature for eggs and larvae. In the experiment 1, hatching rate and larval deformation rate were first compared in eggs incubated in FW, 5, 10, 15, 20 and 30 psu diluted seawater (SW). Marble goby’s eggs tolerated salinities from FW to 15 psu SW with the highest hatching rate at 10 psu SW (60.0±2.0%, mean±SD). To understand this phenomena, egg development, hatching periods, hatching rate, larval deformation rate and survival rate were then compared between FW and 10 psu SW. In 10 psu SW, significantly higher hatching rates and lower deformation rates were observed compared to FW. Embryonic development was similar in both salinities, but in FW, hatching was delayed and all larvae died by 10 days after fertilization (dAF). Peak hatching in 10 psu SW (33.1±5.6%) and FW (10.6±3.4%) were observed in 48-60 and 72-84 hAF, respectively. Larvae hatched in later period had higher deformation rates. The eggs incubated in 10 psu SW had a shorter hatching period, higher hatching rate and better larval survival. The results suggested egg incubation in 10 psu SW for seed production of marble goby. In the experiment 2, I compared the developments of morphology, sensory organs and behavioural changes of larvae reared in FW and 10 psu SW to determine the cause of larval mortality in FW. Newly hatched larvae weresimilar in size in both salinities; 3.0±0.1 mm in length with yolk sac volume 0.052±0.005 mm3 at 1 day after hatching (dAH). There was no apparent difference in larval morphology and behaviour in both waters during the first three days. Remarkable changes were noticed after first feeding was commenced. Larvae in FW become inactive and were unable to feed while larvae in 10 psu actively foraged and fed. These larvae showed similar development in sensory organs. Histological analyses of gut epithelium of larvae at 9 dAH revealed remarkable difference in two salinities. The gut of larvae reared in FW was significantly thinner (9.0±2.8 μm) compared to those in 10 psu SW (23.7±3.3 μm). All larvae in FW died at 9 dAH while the survival rate in 10 psu SW was 69.0±2.0%. The results indicated that larvae in FW were unable to feed as well as the larvae did in 10 psu SW and the larvae were considered required brackish water physiologically. In the experiment 3, I compared embryo mortality, hatching rates, deformation rates, hatching periods, and larval growth and survival at different temperatures. Over 70% eggs died in 24 °C, but normal development and hatching was observed in temperature from 26°C to 32°C. Hatching period negatively correlated with incubation temperature with the fastest hatching period of 48 hours at 32°C. Higher temperatures hastened the egg development, hatching time and period. The highest survival was observed at 28°C (56.0±4.0%), followed by 30 °C (46.0±2.0%), then significantly lower at 26 °C (30.0±2.0%) and 32 °C (26.0±3.6%). These results showed the suitable incubation temperature ranged from 28 to 32 °C and early larval rearing at 28°C was recommended for marble goby. These experiment results indicated that egg incubation and larviculture of marble goby should be conducted using 10 psu SW with temperature between 28°C to 32°C, preferably 28°C for early larval rearing. Both methods are applicable on egg and larval survival and contributed to enhance the seed production of marble goby. However, the result is based on the eggs and larvae obtained from the brood stock captured in the river. The landlocked population may require different salinity and/or temperature for embryonic and larval development. Determination of population is likely important for application of the present data in egg incubation and larviculture of marble goby.